The experience of comparing the variations of the induction vector in magnetically conjugate points - I. Rokityansky; V. Babak; A.V. Tereshyn (Геофизический журнал, 2017)
Processing was performed and graphs of induction vector change were obtained from 1991—2005 to 2014 on 12 pairs of magnetically conjugated observatories located on all continents and some islands in the geomagnetic latitude range from +82,73° to –78,91°. The annual variations of the induction vector were separated and analyzed, and global variations of the amplitude of annual variations were obtained. At high latitudes the annual variations of the induction vector can reach 0,5, in the middle and low latitudes they are almost an order smaller. It is also determined that the amplitude of annual variations increases with the period and that it does not correlate with the magnitude and direction of the induction vector. At two low-latitude observatories located in the north of South America and in Australia after 2008 a synchronous almost two fold increase in the amplitude of the annual variation was found, which may be a manifestation of some global process. A clearly pronounced effect associated with the position of observatories in the conjugate regions at this stage was not revealed.